La Potencialidad Turística En Los Proyectos De Turismo Rural Comunitario - Santamaría, Gabriela Estefanía Román; Vintimilla, Mónica Cecilia Zurita; Romero, Gabriela Natalí Fonseca; Vizuete, Danny Daniel Castillo; Báez, Luis Alberto Quevedo (European Scientific Journal, ESJ, 2017)
Tourism is one of the main productive sectors that allow the improvement of the economy in diverse territories. The community of Guasuntos is regarded as a territory with natural and cultural scenic importance. The same, however, can be used in the development of tourism projects with the challenge of turning it into a competitive tourist destination. This was an alternative for local development in generating wealth in favor of the population, fostering the systemic competitiveness of the territory, and generating a guiding process that coordinates public, private, and community efforts. In order to involve the community in the development of this productive activity, an analysis of the situational diagnosis was carried out. Here, information was collected on the biophysical, sociocultural, economic productive components, political human settlement, mobility, energy, and institutional connectivity. In the territory, the inventory of natural and cultural attractions was carried out. This was done using the methodology proposed by the Ministry of Tourism (MINTUR). Finally, the characterization of the tourist demand was carried out. The tourist demand helps to identify the potential market with the consumption capacity of the product. The evaluation of the tourist potential in the territories allows for the identification of the vocation. However, this became a starting tool for the formulation of projects and a planning tool that contributes to the conservation of resources and the implementation of any activity. In addition, it ensures a potential and orderly use of them and serves as a developmental support for the population.